Synbiotic Soygurt Tempe Extract as A Functional Beverage - Harti, Agnes Sri; Irdianty, Mellia Silvy; Muhlishoh, Arwin; Sutanto, Yusup Subagio (PT Inovasi Pratama Internasional, 2024)
Synbiotic tempeh extract soyghurt is a Krenova (creative and innovative) food product because it is novelty and unique as healthy and safe food, functional food, fun for diet and one for all. The result of probiotic fermentation of Lactic Acid Bacteria (LAB) and based on synbiotic tempeh extract (rice bran and chitosan) which has multifunctional anti-hyperglycemia and anti-hypercholesterolemia properties. Research objective: to analyze the effectiveness of synbiotic tempeh soyghurt as a functional drink. The research method analyzes the nutritional content and quality of synbiotic tempeh soygurt products which refer to SNI 7552:2009 concerning flavored fermented milk. Data analysis used bivariate and multivariate Anova tests. The Hedonic test results showed a semi-solid texture, white color, synbiotic tempeh extract aroma, sour taste in the formulation with the addition of 15% skim milk, 1% chitosan, 1:1 ratio LAB starter mix and 5% inoculum. The results of physical chemical and mycobiological quality tests show that the synbiotic tempeh extract meets the quality test as a functional drink.